Etik Dan Profesionalisme Perawat Dan Bidan Puskesmas Marawola Kabupaten Sigi Pada Masa Tanggap Bencana Gempa Bumi - Nasrun, Nasrun; Fathya, Fathya (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2021)
Palu city, Donggala, was hit by a 7.4 scale earthquake followed by a tsunami and liquefaction in September 2018. Numerous casualties were reported, particularly Maralowa health centre, Sigi district. Medical personnel should strictly adhere to their competencies. However, it is not uncommon to act beyond their capacity during a natural disaster. We are interested in investigating the ethical issues and professional aspect of medical personnel during an emergency. The research was conducted from March to June 2020, with qualitative methods using in-depth interviews of 8 participants who lived in Marawola Health Center at the time of the earthquake disaster. We used the Miles and Huberman method (1992) for data analysis. Medical personnel experienced a heavy load of working burden and psychological pressure; they were even unprepared for this condition. Overlapping competency is happening among medical personnel, but we did not found any ethical issues nor professionals breach during practice in Marawola Health Center